Implementation of Problem-Based Learning with Ethnomathematics to Enhance Students’ Mathematical Literacy: A Systematic Review and Bibliometric Analysis (2020-2025) - Sakdiyah, Siti Khalimatus (Media Pendidikan Matematika, 2025)
Education in Indonesia continues to face various challenges, one of which is the low level of mathematical literacy. Mathematical literacy reflects the extent to which students are able to understand, formulate, and apply mathematical concepts appropriately to interpret information and solve problems in real-life contexts. One possible effort to overcome this issue is through the implementation of the Problem-Based Learning (PBL) model with an ethnomathematics approach, which integrates local cultural contexts into the process of mathematical problem solving. This study aims to analyze research trends and the implementation of the PBL model with an ethnomathematics approach toward students’ mathematical literacy during the period of 2020-2025. The method used is a Systematic Literature Review (SLR) combined with bibliometric analysis using the VOSviewer software and a review of nine articles that met the inclusion and exclusion criteria. The results indicate that research on PBL-ethnomathematics has increased over the years, focusing on developing mathematical literacy through culture-based learning, and the implementation of the PBL model with an ethnomathematics approach has been proven effective in enhancing students’ mathematical literacy.